(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Today Indian Pharma Industry lives in a VUCA environment. (Volatile, Uncertainty, Complexity, and Ambiguity). To succeed in this changing environment, companies not only need to be agile but continuously need to monitor global trends and adapt swiftly. The major challenge for the Industry and the organization is to identify, develop and retain the executives with the best talents. The complexity of the business environment requires organizations with managerial skills that have high a Emotional Quotient to achieve higher performance. To achieve high performance, it is very important to cope with Stress related to Job Performance. Thus it becomes important to develop Emotional Intelligence. The Indian Pharmaceutical industry is a knowledge-based industry and human resource is an asset for the organization. Thus this study looks into how emotional intelligence helps employees to increase their job performance. It also tries to ascertain whether the relationship is mediated by Organization Role Stress. A theoretical model was created and a hypothesis was generated to understand the relationships. Survey of executives. i.e. managers working in Indian Pharmaceutical companies from all departments were conducted in Mumbai through a questionnaire. Hypothesis testing was done through correlation and regression to see the relationship and its significance. R square was calculated to see the mediation effect. Kolmogorov-Smirnov tests were done to check the normality of the data. A p-value of less than 0.05 for this research paper. Hypothesis testing for demographic factors was conducted through non-parametric tests such as Mann – The Whitney U test and Kruskal -Wallis Test. All the factors of Emotional Intelligence like Self-Awareness, Self-Management, Social Management, and Relationship Management had a negative and significant relation with Organization Role Stress This study shows if Emotional Intelligence is developed in the managers of Indian Pharmaceutical companies and provided training, it will create awareness and sensitivity among managers to distinguish the feelings underlying interpersonal communication, and resist the temptation to respond impetuously and thoughtlessly. This helps an employee to manage Organization Role Stress and increase job performance.